Skupni magistrski študij Erasmus Mundus za obvladovanje poplavne ogroženosti (FLOODRisk) - Brilly, Mitja (Gradbeni vestnik, 2019)
Integrated flood risk management aims at reducing the human and socio-economic losses caused by flooding, while at the same time taking into account the benefits from floods and the use of flood plains or coastal zones. The need for the adoption of a holistic integrated approach to managing flood risks is reflected in the Flood Directive of the European Parliament. Students start the 2-year programme at TU Dresden where they complete their first semester with 30 ECTS with courses on hydro-meteorological processes and global change and its impacts. Then the students move to IHE for their second semester with 30 ECTS, where they receive courses on modelling and computer-based tools for planning, forecasting and decision support. Subsequently, the students move to UPC Barcelona to follow part of their third semester with 20 ECTS with courses on hazards due to flash floods, debris flows, and coastal flooding. The University of Ljubljana, where students follow courses on spatial planning and socio-economic and institutional frameworks of flood risk management to earn 10 ECTS, hosts the last part of the third semester. Each semester provides several electives and there are international fieldtrips. The programme received funding from the Erasmus+ programme of the European Commission (EC) from 2010 to 2015, and has succeeded in further funding for the period from 2019 to 2024.
Keywords: Erasmus Mundus; flood risk management; geneErasmus Mundus; joint master programme; obvladovanje poplavne ogroženosti; skupni magistrski študij